Use of intravitreal dexamethasone implants in the treatment of diabetic macular edema: Expert recommendations using a Delphi approach. Issue 5 (September 2020) - García Layana, Alfredo; Adán, Alfredo; Ascaso, Francisco Javier; Cabrera, Francisco; Donate, Juan; Escobar Barranco, José Juan; Peralta, Gema; Reyes García, Rebeca; Rodríguez Maqueda, Mariano; Ruiz-Moreno, José María; Vinagre, Irene; ,
Objective: The aim of this study is to develop guidance on the use of intravitreal dexamethasone implants in the treatment of diabetic macular edema. Method: The study was performed using the modified Delphi method to obtain a consensus among a panel of experts on management of patients with diabetic macular edema and use of intravitreal dexamethasone implants in clinical practice. Thirty-seven panel members, experts on retina, from different Spanish centers were invited to participate. Individual and anonymous opinions were asked by answering a 76-item questionnaire across 11 topic areas (two rounds were done). Level of agreement was assessed using a Likert-type scale of 9 points. Results: Agreement on "consensus" was reached during the first round in 63 items. The 13 remaining items underwent a second round of voting. After the second round, agreement on "consensus" was reached on five items. Finally, eight items remained without consensus. Conclusion: Intravitreal dexamethasone implants are useful in the treatment of patients with diabetic macular edema with different profiles, for example, pseudophakic, poor-adherents, vitrectomized, candidates for cataract surgery, patients with high inflammatory component, and with a history of cardiovascular events. The use of intravitreal dexamethasone reduces the number of visits and facilitates compliance. Experts thought that the switch from anti-vascular endothelial growth factor therapy to intravitreal dexamethasone implants should be done preferably after three injections. Also, pro re nata treatment provides better results in diabetic macular edema patients as it helps to prevent undertreatment. Finally, experts concluded that clinical guidelines and treatment protocols for diabetic macular edema need to be updated.